The role of company size in moderating capital intensity and manager ability to tax avoidance - Qurrotulayni, Nadia; Masripah, Masripah (Educoretax, 2025)
This study was conducted to examine the effect of capital intensity and managerial ability on tax avoidance by adding company size as a moderating variable, and profitability and leverage as control variables. This study is a quantitative study with a random effect model. The sample selection used purposive sampling with a total of 252 samples from 84 manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2021 – 2023 period. The hypothesis test used was multiple linear regression using STATA 14. Based on the results of the hypothesis test, it shows that (1) capital intensity has no effect on tax avoidance, (2) managerial ability has an effect on tax avoidance, (3) company size has no effect in strengthening the relationship between capital intensity and tax avoidance (4) company size has no effect in strengthening the relationship between managerial ability and tax avoidance.This indicates that tax avoidance efforts are influenced more by managerial skills than investments in fixed assets. This emphasizes the importance of the role of management in tax planning, so regulators need to focus more on increasing supervision of tax policies related to managerial ability.